Erythorbyl laurate suppresses TNF-α-induced adhesion of monocytes to the vascular endothelium. (May 2021) - Ha, Su Jeong; Kim, Min Jeong; Park, Joon; Choi, Hyun-Wook; Yu, Hyunjong; Chang, Pahn-Shick; Jung, Sung Keun
Graphical abstract: Highlights: Oral administration of EL ameliorated TNF-α-induced vascular inflammation. Oral administration of EL inhibited TNF-α-induced monocyte infiltration in the aortic root. Oral administration of EL inhibited TNF-α-induced production of inflammatory cytokines including IL6 and TNFA in mice aorta. EL diminished TNF-α-induced phosphorylation of MAPK and NF-κB signaling molecules. EL suppressed TNF-α-induced TAK1 phosphorylation in HUVECs. Abstract: Erythorbyl laurate (EL) can be produced via lipase-catalyzed esterification between erythorbic acid and lauric acid. In this study, we evaluate the anti-inflammatory effect of EL in the early stage of atherosclerosis. EL suppressed tumor necrosis factor (TNF)-α-induced monocyte adhesion to vascular endothelial cells and expression of vascular cell adhesion molecule (VCAM)-1 in human umbilical vein endothelial cells (HUVECs). Additionally, EL suppressed TNF-α-induced p65/IκB kinase (IKK)/IκB phosphorylation in HUVECs. Western blot analysis of cytosolic and nuclear cell fractions and immunofluorescence showed that EL suppressed TNF-α-induced translocation of p65 from the cytoplasm to the nucleus. EL also inhibited phosphorylation of extracellular-signal-regulated kinase (ERK) 1/2, p38, and c-Jun N-terminal kinases (JNK) 1/2 in HUVECs. EL suppressed TNF-α-induced phosphorylation of Akt, IRAK1, and TAK1 in HUVECs. Quantitative RT-PCR analysis showed that EL significantly suppressed TNF-α-induced interleukin (IL)1B, IL6, TNFA, and CCL2 mRNA expression in HUVECs. Additionally, oral administration of EL suppressed TNF-α-induced IL6 and TNFA expression in the mouse aorta. EL could represent a promising functional nutrient that can be ingested for the prevention of vascular inflammation via decreased monocyte infiltration to the vascular endothelium and suppression of inflammatory nuclear factor (NF)-κB and mitogen-activated protein kinases (MAPKs) signaling pathways.